The effects of HIV/AIDS on agricultural production systems in Zambia: A restudy 1993-2005 - Drinkwater, Michael; McEwan, Margaret; Samuels, Fiona (International Food Policy Research Institute, 2006)
This analytical report is the outcome of a restudy that was undertaken in January 2005 of an original study undertaken in 1993 of the impact of HIV/AIDS on agricultural production systems and livelihoods in the Mpongwe area of the Copperbelt Province and the Teta area of Serenje District in the Central Province in Zambia. The study has used a ‘cluster analysis’ methodology that allows individuals and households to be seen in context, and in its remapping of the clusters originally surveyed has allowed surprising insights into the dynamics of social change to be developed. There are significant contrasts between the two study sites. In Mpongwe, a major maize production centre near the Copperbelt markets, maize production, dependent on agricultural inputs, has become the dominant production activities and fuelled a growing inequality between those successful in securing access to the necessary inputs, including draft power, and those who cannot. By contrast, in the Teta area, market liberalisation has deprived the area of access to inputs, and in this system maize production has declined, and the farming systems now consists of diverse food crops, not dependent on external inputs.